2003
DOI: 10.1080/0968768021000055698
|View full text |Cite
|
Sign up to set email alerts
|

The fence and picket structure of the plasma membrane of live cells as revealed by single molecule techniques (Review)

Abstract: Models of the organization of the plasma membrane of live cells as discovered through diffusion measurements of integral membrane molecules (transmembrane and GPI-anchored proteins, and lipid) at the single molecule level are discussed. Diffusion of transmembrane protein and, indeed, even lipid is anomalous in that the molecules tend to diffuse freely in limited size compartments, with infrequent intercompartment transitions. This average residency time in a compartment is dependent on the diffusing species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 13 publications
3
145
0
4
Order By: Relevance
“…Both membrane proteins and lipids undergo anomalous diffusion in different cells including human embryonic kidney, neurons, Chinese hamster ovary, Cos7, fibroblasts, keratinocyte, mouse hepatoma (HEPA-OVA), sperm, and HeLa (James, Hennessy, Berge, & Jones, 2004;Kusumi et al, 2005;Manley et al, 2008;Murase et al, 2004;Ritchie, Iino, Fujiwara, Murase, & Kusumi, 2003). Further, anomalous diffusion of membrane proteins was also observed in living animals such as zebrafish (Schaaf et al, 2009).…”
Section: Evidence For Anomalous Diffusion In the Plasma Membranementioning
confidence: 86%
“…Both membrane proteins and lipids undergo anomalous diffusion in different cells including human embryonic kidney, neurons, Chinese hamster ovary, Cos7, fibroblasts, keratinocyte, mouse hepatoma (HEPA-OVA), sperm, and HeLa (James, Hennessy, Berge, & Jones, 2004;Kusumi et al, 2005;Manley et al, 2008;Murase et al, 2004;Ritchie, Iino, Fujiwara, Murase, & Kusumi, 2003). Further, anomalous diffusion of membrane proteins was also observed in living animals such as zebrafish (Schaaf et al, 2009).…”
Section: Evidence For Anomalous Diffusion In the Plasma Membranementioning
confidence: 86%
“…First, accumulating evidence supports a dominant role of the subcortical actin in compartmentalizing proteins in the PM [8,195,198,251]. Second, some of the many treatments to modify cholesterol levels in the PM, as depletion or loading of cholesterol with 54 cyclodextrin have a direct effect on the dynamics or polymerization state of subcortical actin in living cells [6,252,253].…”
Section: Discussionmentioning
confidence: 98%
“…In a series of additional experiments the same group followed the movement of lipids and membrane proteins with a temporal resolution of up to 40,000 Hz [185]. This revealed that also lipids in the outer leaflet of the PM were subject to confined diffusion [194] and that the lipids and particles were trapped in these cages for 1 -5 ms before they would hop to a neighboring cage [195,196]. The Kusumi group subsequently showed that GPI-anchored proteins (like GPIlinked MHC II) exhibit this distinct hop-diffusion behavior like other phospholipids and TM proteins [197].…”
Section: Diffusion Of Cholesterol Probes In the Pm Studied By Sptmentioning
confidence: 96%
“…[1][2][3] It reveals dynamic subpopulations and opens the possibility of studying the full statistical distributions of the transport process. Anomalous subdiffusion has been found to be common in the plasma membrane [4][5][6] with important implications for protein complex formation 7 and it implies that the plasma membrane is a complex and crowded environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been suggested as the source of the observed anomalous subdiffusion: obstruction by the membrane skeleton and its bound proteins, 6 inclusion or exclusion from lipid domains, 8 binding to immobile traps, 9,10 or a combination of the above. 11,12 Single particle tracking experiments to date could not directly image the obstacles to diffusion but only deduce their physical properties from the diffusion data.…”
Section: Introductionmentioning
confidence: 99%